Development of an experimental model using cold stress to assess the pathogenicity of two Moroccan AI H9N2 isolates from 2016 and 2022 in commercial broiler chickens - Oumayma Arbani; Mariette F. Ducatez; Mireille Kadja-Wonou; Faiçal Salamat; Faouzi Kichou; Mohamed El Houadfi; Siham Fellahi (PLoS ONE, 2025)
Since 2016, low pathogenic avian influenza virus (LPAIV) H9N2 became a major issue for poultry production in Morocco. Even though the agent was classified as low pathogenic, AI H9N2 cause significant economic losses, particularly during co-infections. Experimentally, it has been difficult to reproduce the clinical picture without appealing other viral or bacterial pathogens. Our study was carried out to evaluate a new challenge model using cold stress in commercial broilers infected with two Moroccan H9N2 viruses isolated in 2016 and 2022. One hundred twenty day-old chicks were divided into four groups: A, B, and C exposed to cold stress, and D was kept as negative control. At 21 days of age, Groups A and B were challenged by oculo-nasal route with 107 EID50 of H9N2 strains, isolated respectively during 2016 and 2022. Meanwhile, chicks of group C were exposed to only cold stress. The assessment of body weight gain, clinical signs, lesions, mortality, and oropharyngeal viral shedding was monitored for 15 days post-challenge. Results showed that cold stress exacerbated H9N2 clinical signs, allowing us to establish a scoring system and to validate the challenge model without co-infections. Gross and microscopic lesions, induced by the virus primarily in the respiratory tract, peaked at 5 dpi and significantly decreased at 15 dpi. Group B harbored the highest viral loads with viral shedding persisting beyond 11 dpi in both groups. This study demonstrates a clear clinical difference among the two isolates; A/chicken/Morocco/178-2/2022(H9N2) showed a significant increase in virulence compared to the firstly isolate A/chicken/Morocco/SF1/2016(H9N2). The novel H9N2 challenge model using cold stress will contribute to a better understanding of LPAI pathogenesis and epidemiology and allow for research closer to the field.